Contextual Attribute Variables in the Use of ICT in Primary Level Students from Southern Sonora, Mexico - Sonia Verónica Mortis-Lozoya; Jesús Tánori Quintana; Joel Angulo Armenta; Marisol Villegas Pérez (Universidad de Navarra, 2018)
The aim of this study is to establish the relation between the contextual attribute variables in fifth and sixth grade students' use of ICTs through a logistic regression model. A sample of 522 students was randomly selected out of a non-probabilistic sample of 1865 students in 14 primary schools from southern Sonora, Mexico, from which two sub-samples were selected, one made of 261 students who use ICTs and another made of 261 students who don't. Results showed that the predictor variables: type of school, Internet at home and having an e-mail account, show significant differences between groups of students who make basic use of ICTs and those who don't.